2021
DOI: 10.3390/jpm11050367
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Omeprazole and Gliclazide in Relation to CYP2C19 Phenotype

Abstract: The antidiabetic drug gliclazide is partly metabolized by CYP2C19, the main enzyme involved in omeprazole metabolism. The aim of the study was to explore the interaction between omeprazole and gliclazide in relation to CYP2C19 phenotype using physiologically based pharmacokinetic (PBPK) modeling approach. Developed PBPK models were verified using in vivo pharmacokinetic profiles obtained from a clinical trial on omeprazole-gliclazide interaction in healthy volunteers, CYP2C19 normal/rapid/ultrarapid metabolize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…In the first case (benzodiazepine + venlafaxine), caution is recommended with this association because it may increase the incidence and severity of ADRs [ 55 ]. In the second one, omeprazole may augment the risk of hypoglycemia associated with gliclazide in most patients, as the oral antidiabetic is metabolised by CYP2C19, and omeprazole is an inhibitor of this enzyme [ 56 ]. Finally, the interaction known as the triple whammy (angiotensin converting enzyme inhibitors/angiotensin-II receptor blockers (ACEI/ARBs) + diuretic + nonsteroidal anti-inflammatory drugs (NSAIDs)) was detected by CheckTheMeds, but not by the other two databases, which worked only with pairs of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In the first case (benzodiazepine + venlafaxine), caution is recommended with this association because it may increase the incidence and severity of ADRs [ 55 ]. In the second one, omeprazole may augment the risk of hypoglycemia associated with gliclazide in most patients, as the oral antidiabetic is metabolised by CYP2C19, and omeprazole is an inhibitor of this enzyme [ 56 ]. Finally, the interaction known as the triple whammy (angiotensin converting enzyme inhibitors/angiotensin-II receptor blockers (ACEI/ARBs) + diuretic + nonsteroidal anti-inflammatory drugs (NSAIDs)) was detected by CheckTheMeds, but not by the other two databases, which worked only with pairs of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that omeprazole might increase the risk of hypoglycemia in most patients treated with gliclazide. [13] Several studies have shown the presence of H. pylori infection affects the incidence of insulin resistance and metabolic syndromes [14]. Furthermore, H. pylori treatment can improve the mean level of glycosylated hemoglobin in patients with type 2 diabetes [10].…”
Section: Discussionmentioning
confidence: 99%
“…PPIs can significantly raise serum gastrin concentration and affect glucose metabolism by promoting B-cell regeneration and expansion; PPIs can therefore increase the risk of hypoglycemia. Another study showed that omeprazole might increase the risk of hypoglycemia inpatients treated with gliclazide [ 18 ].…”
Section: Discussionmentioning
confidence: 99%